Application of postharvest chemical treatments to enhance storage and shelf life of pomegranate fruit (cv. Wonderful) - Atukuri, Julian (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc Food Sc)--Stellenbosch University, 2017.